Biochemical and antibacterial properties of Thai medicine herbal infusions - Chunthanom P. (2014)
Biochemical and antibacterial properties of Thai medicine herbal extracts including chrysanthemum, lotus stamen, bullet wood, cananga, safflower, roselle and licorice as well as cashew flower, leaf buds and leave were investigated. It was found that dried cashew flower, leaf buds and leave extracts contained highest amount of total phenolics, tannin and 2,2-diphenyl-1-picrylthydrazyl (DPPH) radical inhibition compared to the other herbs. Escherichia coli inhibition of cashew flower, cashew leaf buds and cashew leave extracts was higher than others. The flavored herbal infusion, mixture of cashew flower, licorice root, cashew leaf buds and cashew leave (7:1.25:1.25:0.5 by weight), had high quantities of total phenolics, tannin and antioxidant capacity (DPPH assay) as well as antibacterial activity than those of Thai green tea extract. In overall the highest antimicrobial activity occurred in flavored herbal infusion was related with the highest tannin content and acidity. © All Rights Reserved.